YOUTH CENTER DI KOTA PONTIANAK - Artha, Dita Ollivia; Gultom, Bontor Jumaylinda; Kalsum, Emilya (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Adolescence is a period of development from children to adults. Adolescents have various characteristics in their development. Lack of facilities and guidance for adolescents causes juvenile delinquency behavior, while adolescence is a very important period because of the process of forming individual characters. Youth need a place that can nurture and develop their potential. Youth-oriented forum, namely the Youth Center. The design of the Youth Center must facilitate the function of the building while taking into account the characteristics of youth in Pontianak City. The design of the Youth Center used a descriptive method, namely the description of literature and theory. The stages in the design method begin with collecting data, then the data is analyzed to form a concept that produces a product in the form of a design image. The design of Youth Centers in Pontianak City has creative, reacreative and educational functions. The design location is at the intersection of A. Yani street and MT. Haryono street with an area of +5,877 m2. The building consists of four floors, the first floor consists of public spaces, the second floor contains a sports area, then on the third floor there is a play area, while the fourth floor consists of educational spaces. The results achieved were building design based on building functions based on the activities and characteristics of youth in Pontianak City.